Does bribery in the home country promote or dampen firm exports? - Lee, Seung‐Hyun; Weng, David H. (Strategic Management Journal, 2013)
This study examines the impact of bribery within the home country on firm exports by developing two contrasting hypotheses. On the one hand, preferential treatment resulting from government officials in exchange for bribes may promote exports by enhancing efficiency and enabling bribing firms to better compete in foreign markets. On the other hand, preferential treatment resulting from bribes may decrease exports by providing firms with more established positions within the domestic market diminishing the incentive to explore foreign markets. Adopting the three‐stage least squares method, we test these competing arguments using a sample of firms operating within transition economies. We find that bribery within the home country decreases rather than increases firm exports. The implications of our findings are discussed . Copyright © 2013 John Wiley & Sons, Ltd.